HUBUNGAN KEMAMPUAN TEKNOLOGI INFORMASI KOMUNIKASI (TIK) TERHADAP HASIL BELAJAR MENGGAMBAR DENGAN PERANGKAT LUNAK (MDPL) SISWA KELAS XI JURUSAN TEKNIK DESAIN PEMODELAN DAN INFORMASI BANGUNAN (TDPIB) DI SMK NEGERI 1 SUMATERA BARAT - Anggara Sukhma Putra Surya; Dr. Fahmi Rizal, M.Pd, M.T (Universitas Negeri Padang, 2019)
Abstract—This study aims to determine the relationship between Information and Comunications Technology (ICT) capabilities and Learning Drawing With Software (MDPL) Class XI Building Engineering and Modeling Information Design Department (TDPIB) at SMK Negeri 1 Sumatera Barat. This type of research is a correlation research with a population of 30 students and using the technique of Total Sampling. The types of data used are primary and secondary data. Primary data is obtained through Exams, while secondary data is learning outcomes MDPL subject at SMK Negeri 1 Sumatera Barat on June - December 2018. Data analysis techniques used are: 1) Descriptive Analysis, 2) Normality Test, 3) Linearity Test and 4) Hypothesis Test. The results of this study concluded that there is a high relationship between ICT capabilities and MDPL Class XI Building Engineering and Modeling Information Design Department (TDPIB) at SMK Negeri 1 Sumatera Barat. Keywords: ICT Ability, MDPL, Learning Outcomes